HOUSING THE REMAINS OF CULTURE: ABSOLUTE MONUMENTS TO ABSOLUTE KNOWLEDGE - Grossman, Marshall (Surfaces, 1992)
A study of the dialectic of desire and commemoration as they constitute the discourse of cultural nostalgia in the poetry of John Donne.